2020
DOI: 10.22541/au.159164082.23388668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Advances and novel developments in environmental influences on allergic diseases

Abstract: Atopic diseases have increased in prevalence over the last few decades and the rapid increases suggest that the predominant driving forces behind these increases are environmental factors rather than genetic alterations. A number of environmental factors have been implicated in the increased prevalence of allergic diseases. Predominant among them are increased exposure to pollutants and decreased exposure to microbes and parasitic infections. The hygiene hypothesis suggests that increased hygiene and lack of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Other studies have also demonstrated that high concentrations of outdoor air pollution can have a direct in ammatory and irritating effect on the airway epithelium, thereby increasing the likelihood of asthma attacks [45] . Air pollutants have been found to contribute to atopic diseases through various mechanisms, including skin barrier dysfunction, oxidative stress induction, epigenetic modi cation, and altered immune cell responses [46][47][48][49] . One such mechanism involves the exposure of human nasal epithelial cells to PM 2.5 , which has been shown…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that high concentrations of outdoor air pollution can have a direct in ammatory and irritating effect on the airway epithelium, thereby increasing the likelihood of asthma attacks [45] . Air pollutants have been found to contribute to atopic diseases through various mechanisms, including skin barrier dysfunction, oxidative stress induction, epigenetic modi cation, and altered immune cell responses [46][47][48][49] . One such mechanism involves the exposure of human nasal epithelial cells to PM 2.5 , which has been shown…”
Section: Discussionmentioning
confidence: 99%